Automatic reference evapotranspiration data acquisition system coupled to a constant greater table lysimeter (Research, Society and Development, 2023)
Evapotranspiration is a very important agrometeorological element in the agricultural environment for irrigation management. The correct measurement of evapotranspiration is difficult to obtain due to the complexity of its measurement instrumentation and the need for daily monitoring to collect measurements. In view of this scenario, the purpose of this study was to develop an automated system using embedded electronics through the Arduino free hardware platform, for the measurement of reference evapotranspiration using a constant water table lysimeter. The measurements collected with the constant water table lysimeter were obtained experimentally in the second half of 2017. The results obtained from the graphical analysis demonstrate that the system built using embedded electronics through the Arduino platform proved to be reliable for the measurement in the water table lysimeter constant water table on hourly and daily scale.